2020
DOI: 10.1080/21622965.2020.1726353
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and clinical utility of the executive function inventory for children and adolescents: a large multistage populational study including children with ADHD

Abstract: Executive functions (EF) are a set of high order mental abilities that regulate cognition, emotions, and behavior. This study aims to report the construction and validation of a rating scale instrument for EF in children and adolescents aged from 5 to 18 years (EFICA), as well as to report the results of a comparison between children with ADHD and their peers without it. Thus, we conducted a population-based cross-sectional study relying on a sample composed of 3,284 typical children and adolescents accessed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…Another research that is consistent with the study reported in this article is the report by Parhoon et al (2022) , Arruda et al (2022) , Castagna et al (2019) , Ramos-Galarza et al (2019) , and Bausela (2019) who highlight the importance of this type of executive function scale to analyze the symptoms of attention deficit and hyperactivity disorder to identify developmental disorders and to analyze the role of executive functions in the educational setting.…”
Section: Discussionsupporting
confidence: 85%
“…Another research that is consistent with the study reported in this article is the report by Parhoon et al (2022) , Arruda et al (2022) , Castagna et al (2019) , Ramos-Galarza et al (2019) , and Bausela (2019) who highlight the importance of this type of executive function scale to analyze the symptoms of attention deficit and hyperactivity disorder to identify developmental disorders and to analyze the role of executive functions in the educational setting.…”
Section: Discussionsupporting
confidence: 85%
“…Second, we reported low, but significant, odd ratios, which indicate weak associations between harsh parenting, inhibitory control, and bullying involvement. As our outcome is focused on child behavior at the school setting, while our predictors are more likely reflections on parent and child behavior at home, there might be individual differences in behavior due to the differing demands and environmental structures across these two settings (e.g., Arruda et al, 2020 ). Third, it is likely that parents underreported on harsh parenting.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Nutraceuticals Despite the high expectations of supplements' success in the treatment of pediatric migraine, the positive evidence derives only from open-label trials, while the controlled ones could not demonstrate unequivocal superiority against placebo. Accordingly, some studies are found in the literature regarding riboflavin 50,51 , coenzyme Q10 52 , magnesium 53 , melatonin 54 , butterbur 55,56 and vitamin-D. 57…”
Section: Non-pharmacologic Treatment Behavioral Interventionsmentioning
confidence: 99%